Population Data of D6S1043, Penta D and Penta E Loci in Calabria (South of Italy) - Barbaro,; G. Falcone ,; A. La Marca, (Journal of Basic & Applied Sciences, 2020)
In the present study 200 unrelated healthy natives of Calabria were genetically characterized for D6S1043, Penta D and Penta E STR markers. Allele frequencies distribution and some statistical parameters of forensic interest have been calculated and compared with other published populations data. Results showed Penta E was the most informative locus based on heterozygosity, PIC, PD and TPI, while D6S1043 was the less informative. Our findings confirmed these 3 loci are useful for forensic purposes and paternity tests especially if analyzed in association with other STRs.